Low-Ni steel alloy with hydrogen-induced degradation resistance

By adjusting the ratios of Mn, C, Al, Cr, Cu, Ni and Si in low Ni steel alloys, austenite microstructure with high stacking fault energy is formed, which solves the insufficient hydrogen resistance in high-pressure hydrogen storage applications. The problem of this has achieved cost-effective improvement in hydrogen resistance and mechanical properties.

CN119137302APending Publication Date: 2024-12-13UNITED STATES STEEL CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037095.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-29
Filing Date
2023-04-28
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Due to the high cost of Cr and Ni, the 316L grade austenitic stainless steel used in existing high-pressure hydrogen storage applications is difficult to find cost-effective alternative materials, and its hydrogen resistance is insufficient in the environment of hydrogen deterioration.

Method used

Using a low-Ni steel alloy containing controlled quantities Mn, C, Al, Cr, Cu, Ni and Si, by adjusting the proportion of these elements, an austenite microstructure with high stacking fault energy is formed to avoid Martialis The formation of the body phase can improve hydrogen resistance.

Benefits of technology

It realizes the hydrogen resistance of the material under a high hydrogen environment, avoids the ductility loss and embrittlement caused by hydrogen deterioration, and the mechanical properties are equivalent to or higher than those of 316L stainless steel, reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137302A_ABST
    Figure CN119137302A_ABST
Patent Text Reader

Abstract

The present invention provides a steel alloy having hydrogen-induced degradation resistance comprising controlled amounts of Mn and C, as well as Al, Cr, Cu, Ni and Si. The steel alloy has an austenitic microstructure and a relatively high stacking fault energy, which avoids the formation of a martensitic phase that reduces hydrogen resistance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 336,431, filed on April 29, 2022, which is incorporated herein by reference. Technical Field

[0003] The present invention relates to low Ni steel alloys having good resistance to hydrogen induced degradation during service. Background Art

[0004] Alloys currently used for high pressure hydrogen storage applications include 316L grade austenitic stainless steel, which nominally contains 18 wt% Cr and 13 wt% Ni in addition to iron and several other elements. However, the additions of Cr and Ni are relatively expensive, so lower cost alternatives would be beneficial for hydrogen applications, such as using hydrogen as a fuel for cars, trucks, etc. Summary of the invention

[0005] The present invention provides a steel alloy having resistance to hydrogen-induced degradation, which contains controlled amounts of Mn and C, as well as Al, Cr, Cu, Ni and Si. The steel alloy has an austenitic microstructure and a relatively high stacking fault energy, which avoids the formation of a martensitic phase that reduces hydrogen tolerance.

[0006] One aspect of the present invention is to provide a hydrogen-degradation resistant steel alloy comprising 15 to 30 wt. % Mn, 0.15 to 1 wt. % C, and 0.05 to 3 wt. % Al. The steel alloy has a microstructure comprising at least 99 volume % austenite and has a relative reduction in area of ​​no more than 20%.

[0007] This and other aspects of the invention will become apparent from the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 is a graph showing that a fully austenitic steel with a desired stacking fault energy can be achieved using relatively large amounts of Mn and adding controlled amounts of C, Al and Ni in accordance with the present invention.

[0009] Figure 2 is a graph showing that suitable stacking fault energy is achieved based on Mn content and further additions of Al, Cr, Cu, and Ni according to an embodiment of the present invention.

[0010] Figure 3-6 is a graph of mechanical properties and hydrogen content of a hydrogen-resistant steel alloy of the present invention compared to a standard stainless steel alloy. Figure 3 shows the ultimate tensile strength, Figure 4 shows the yield strength, Figure 5 Shows the total elongation, Figure 6 The relative reduction rate of area is shown.

[0011] Figure 7 and 8 3D graphs of steel alloys of different compositions with varying amounts of Mn and C, and the combined effect on the relative reduction in area of ​​the steel alloys.

[0012] Figure 9-14 are micrographs of a fracture surface of a hydrogen degradation resistant steel alloy of the present invention taken at different locations of the sample before and after electrochemical charging with hydrogen, showing ductile fracture characteristics. DETAILED DESCRIPTION

[0013] The steel alloys of the present invention can be used in hydrogen service because they have relatively high stacking fault energies, for example greater than 20 mJ / m 2 , thereby avoiding the formation of a martensite phase, which would significantly reduce hydrogen resistance. According to the invention, an alloy composition can be selected that stabilizes austenite and avoids martensite formation.

[0014] The hydrogen resistant steel alloy of the present invention may typically contain at least 15 wt % Mn, such as at least 18 wt %, or at least 20 wt %, or at least 20.5 wt %, or at least 21 wt %, or at least 22 wt %. Mn may comprise up to 30 wt %, or up to 25 wt %, or up to 24 wt %. In certain embodiments, Mn may comprise 15 to 30 wt %, or 18 to 25 wt %, or 20 to 24 wt %. Relatively large amounts of Mn may provide qualities similar to stainless steel, including resistance to hydrogen-induced degradation during service. The Mn content results in a fully austenitic steel that is resistant to the degrading effects of hydrogen, such as loss of ductility or embrittlement.

[0015] The hydrogen resistant steel alloy may typically contain at least 0.18 wt % C, such as at least 0.25 wt %, at least 0.3 wt %, or at least 0.4 wt %. C may comprise up to 1 wt %, or up to 0.9 wt %, or up to 0.8 wt %, or up to 0.6 wt %. In certain embodiments, C may comprise 0.18 to 1 wt %, or 0.25 to 0.9 wt %, or 0.3 to 0.8 wt %, or 0.4 to 0.6 wt %.

[0016] The hydrogen resistant steel alloy may typically contain at least 0.05 wt% Al, such as at least 0.1 wt%, or at least 0.5 wt%, or at least 0.8 wt%, or at least 1.0 wt%, or at least 1.2 wt%. Al may comprise up to 2.5 wt%, or up to 2.2 wt%, or up to 2 wt%, or up to 1.8 wt%. In certain embodiments, Al may comprise 0.05 to 2.5 wt%, or 0.8 to 2.2 wt%, or 1 to 2 wt%, or 1.4 to 1.8 wt%.

[0017] The hydrogen resistant steel alloy may typically contain at least 0.5 wt% Si, such as at least 1 wt%, or at least 2 wt%, or at least 2.5 wt%. Si may comprise up to 4 wt%, or up to 3.5 wt%, or up to 3.2 wt%, or up to 3 wt%. In certain embodiments, Si may comprise 1 to 4 wt%, or 1.5 to 3.5 wt%, or 2 to 3.2 wt%, or 2.5 to 3 wt%. In certain embodiments, the steel alloy may be substantially free of Si.

[0018] The hydrogen resistant steel alloy may typically contain at least 0.8 wt % Ni, such as at least 1 wt %, or at least 1.2 wt %. Ni may comprise up to 2.5 wt %, or up to 2 wt %, or up to 1.5 wt %. In certain embodiments, Ni may comprise 0.8 to 2.5 wt %, or 1 to 2 wt %, or 1.2 to 1.5 wt %. In certain embodiments, the steel alloy may be substantially free of Ni.

[0019] The hydrogen resistant steel alloy may typically contain at least 0.2 wt % Cu, such as at least 0.4 wt % Cu, or at least 0.6 wt % Cu. Cu may comprise up to 2 wt %, or up to 1.5 wt %, or up to 1.2 wt %. In certain embodiments, Cu may comprise 0.2 to 2 wt %, or 0.4 to 1.5 wt %, or 0.6 to 1.2 wt %. In certain embodiments, the steel alloy may be substantially free of Cu.

[0020] The hydrogen resistant steel alloy may typically contain at least 1 wt % Cr, such as at least 1.5 wt % Cr, at least 2 wt % Cr, or at least 2.2 wt % Cr. Cr may account for up to 3.5 wt %, or up to 3.2 wt %, or up to 3 wt %, or up to 2.8 wt %. In certain embodiments, Cr may account for 1.5 to 3.5 wt %, or 2 to 3.2 wt %, or 2 to 3 wt %, or 2.2 to 2.8 wt %. Alternatively, Cr may be less than 1.5 wt %, or less than 1 wt %, or less than 0.5 wt %, or less than 0.2 wt %. In certain embodiments, the steel alloy may be substantially free of Cr.

[0021] The hydrogen resistant steel alloy may typically contain at least 0.01 wt % Ti, such as at least 0.05 wt % or at least 0.08 wt %. Ti may comprise up to 0.5 wt %, or up to 0.3 wt %, or up to 0.2 wt %. In certain embodiments, Ti may comprise 0.01 to 0.5 wt %, or 0.02 to 0.3 wt %, or 0.08 to 0.2 wt %. In certain embodiments, the steel alloy may be substantially free of Ti.

[0022] As used herein, the term "substantially free" in reference to alloying additions means that the particular element or material is not intentionally added to the alloy and, if present, is present only in trace amounts as an impurity, such as less than 0.05 wt. % or less than 0.01 wt. %.

[0023] The hydrogen-resistant steel alloy has an austenitic microstructure, wherein austenite accounts for at least 95 volume %, or at least 98 volume %, or at least 99 volume %, or at least 99.5 volume %. In addition to austenite, the hydrogen-resistant steel alloy may be substantially free of other phases, such as ferrite and martensite. For example, if present, such phases are less than 1 volume %, or less than 0.5 volume %, or less than 0.1 volume %, or 0 volume %.

[0024] Figure 1 and 2 The design concept of the present invention is shown. Figure 1 It is shown that a fully austenitic steel with a target SFE range can be achieved using relatively high Mn amounts, such as 22 wt% and 15 wt%, and adding appropriate amounts of C, such as 0.45 wt% C plus Al, Cu and Ni. Alloys with only 0.18 wt% C and 15 wt% Mn cannot meet the design target for SFE. Figure 2 It is further shown that for the carbon and manganese contents investigated, upon further additions of Al, Cr, Cu and Ni, the SFE falls within the desired range.

[0025] Laboratory scale heats of each composition listed in Table 1 were melted, hot rolled and prepared for electrochemical charging to form nascent hydrogen at the sample surface. The electrochemical charging technique was performed as follows: the test samples were electrochemically charged in a 20 g / L Na2SO4 solution at 70°C for 48 hours with the addition of 2 g / L NH4SCN to prevent recombination of nascent hydrogen. A 70 A / m 2 During the electrochemical charging, nascent atomic hydrogen diffuses into the test sample.

[0026] The hydrogen resistance of the hydrogen filled samples can be tested by performing a standard tensile test and comparing the ductility to the unfilled samples. Ductility can be measured using the Reduction of Area (RA). A target Relative Reduction of Area (RRA) of 20% is considered competitive with 316L stainless steel. Therefore, if the RA deteriorates by no more than 20%, the alloy of the present invention is considered competitive with 316L stainless steel from a hydrogen resistance standpoint.

[0027] The following examples are intended to illustrate various aspects of the present invention and are not intended to limit the scope of the present invention.

[0028] Example

[0029] Laboratory melts were produced in a vacuum induction furnace using the actual chemical compositions shown in Table 1.

[0030] Table 1 Melt chemistry

[0031]

[0032] Chemical composition was measured by a LECO C / N / O / S analyzer or by inductively coupled plasma optical emission spectroscopy (ICP-OES). Titanium was added to some melts for microalloying to improve yield strength and possibly reduce the kinetics of twin formation. Low levels of phosphorus (0.015 wt %) and sulfur (0.005 wt %) were added to each alloy to simulate residual phosphorus and sulfur in steel melts. The material was hot rolled from 7 inch thick ingots to 1.25 inch thick slabs in the laboratory and air cooled. All testing was done on hot rolled slabs.

[0033] The samples were measured with a Metis MSAT 30 instrument to determine the percentage of austenite in the material. The results are listed in Table 2 and compared with the 316L stainless steel material used in this study. A fully austenitic structure is ideal for preventing hydrogen embrittlement. Since the samples will be stored in liquid nitrogen to prevent desorption of hydrogen, the samples are also tested after being stored in liquid nitrogen for 24 hours. Except for a reduction of 0.1 volume % in the percentage of austenite in alloys 4 and 6, there is no sign of microstructural change after storage in liquid nitrogen. The alloy is almost a fully austenitic microstructure.

[0034] Table 2 Percentage of austenite in microstructure

[0035] alloy %Austenite % Austenite after LN2 316L SS 99.6 99.6 2 99.7 99.7 3 99.9 99.9 4 99.9 99.8 5 99.8 99.8 6 99.9 99.8

[0036] ASTM E8-22 Specimen 2 circular tensile specimens were tested in the longitudinal direction parallel to the rolling direction according to ASTM E8-22 standard before and after electrochemical hydrogen charging. The extensometer range was exceeded during the test, so the total elongation of all samples was measured manually. The tensile specimens were electrochemically charged in 20 g / L Na2SO4 solution at 70°C for 48 hours with 70 A / m 2 of current density. 2 g / L NH4SCN was added to prevent recombination of nascent hydrogen. The hydrogen test samples were selected from the same melt and close to the same location as the tensile samples to minimize parameters that could affect the amount of hydrogen adsorption (such as grain size). Immediately after the electrochemical hydrogen charging, the tensile samples were stored in liquid nitrogen awaiting tensile testing. Before testing, the tensile sample temperature was delayed for 8 to 12 minutes to stabilize to room temperature. The mechanical properties before and after electrochemical charging were compared, as well as the concentration of diffusible hydrogen from the hydrogen test samples measured at 300°C with a Bruker hydrogen analyzer mass spectrometer.

[0037] Table 4 and Figure 3-6 The mechanical property results before and after electrochemical charging and hydrogen concentration are shown in Figure 2, compared with 316L stainless steel. It is speculated that the higher hydrogen concentration in 316L stainless steel may be due to microstructural differences such as grain size and ferrite percentage compared to the hot rolled alloy in this study. The mechanical properties are comparable or higher than 316L stainless steel in terms of strength and total elongation. Alloys 2, 3, 4 and 6 have a relative reduction of area (RRA) of less than 20%, with Alloy 3 performing the best. Alloy 5 has an RRA of 23.2%, which has lower carbon and manganese levels of 0.2 wt% and 16.5 wt%, respectively. Increasing the manganese level to 20.5 wt% in Alloy 2 increases the average RRA to a value of 11.8%, and increasing the carbon level to 0.48 wt% in Alloy 6 increases the RRA to an average of 14.1%. Increasing both carbon and manganese levels to 0.48 wt. % carbon and 24.0 wt. % manganese further increased the RRA of Alloy 3 to an average of 2.6% and that of Alloy 4 to an average of 11.3%.

[0038] Figure 7 and 8 The effects of Mn and C contributions to RRA are intuitively shown. Figure 7 and 8 The data in show that RRA decreases with increasing concentrations of C and Mn, and that Mn and C each contribute to RRA. The addition of titanium to Alloy 4 increases tensile strength and yield strength compared to Alloy 3, and also increases the RRA value.

[0039]

[0040] Hydrogen induced cracking (HIC) and sulfide stress cracking (SSC) testing was completed on Alloy 4 according to NACE TM0284-2016 and NACE TM0177-2016—Method A, respectively. The stress applied during the SSC testing was 85% of the actual yield stress to simulate a higher hydrogen pressure environment. No cracks were present after each test. Some pitting was observed during the SSC testing.

[0041] Table 4 Sulfide stress cracking (SSC) test

[0042]

[0043] Specification: NACE TM0177-2016—Method A

[0044] Test environment: NACE TM0177 solution A, pH = 2.7, 100 mol% H = S

[0045] Test specimen:

[0046] Type: Standard Finishing Process: Grinding

[0047] Oriented Longitudinal Loading Method: Verification Ring

[0048] * Mark the indicator on the scale. Check the cross section and no SSC is observed.

[0049] The microstructure of the electrochemically charged tensile fracture shows ductile fracture characteristics over the entire fracture surface in both the uncharged and hydrogen-charged samples. Fig. 9 and 10 ), one quarter ( Fig.11 and 12 ) and the center ( Fig.13 and 14 ) obtained the microstructure of the fracture surface of Alloy 6 before and after electrochemical hydrogen filling.

[0050] The low Ni austenitic steel grade designs proposed in this study have carbon levels of 0.18 wt% to 0.5 wt% and manganese levels of 16.5 to 24.5 wt%, as well as Al, Cr, Cu, Ni and Si levels that have been shown to be resistant to hydrogen embrittlement, producing results of less than 20 wt% RRA after electrochemical charging to introduce nascent hydrogen atoms. Based on this study and literature review, materials with carbon levels of 0.18 to 0.6 wt%, manganese levels of 16 to 30 wt%, chromium levels of 2.0 to 3.5 wt%, copper levels of 0.6 to 2 wt%, nickel levels greater than 0.9 wt% for cost reduction purposes (with 1.3 wt% as a target), silicon levels of 2.0 wt% to 4.0 wt%, and aluminum levels of 0.04 wt% to 2 wt% are shown to be suitable affordable low Ni austenitic replacements for 316L stainless steel in terms of resistance to hydrogen-induced degradation. In this study, low carbon and low Mn steel grades are more susceptible to hydrogen embrittlement. Titanium can be used to improve mechanical properties, but it can also increase the material's susceptibility to hydrogen embrittlement.

[0051] As used herein, the terms "comprising", "containing", etc., should be understood as synonymous with "comprising" in the context of the present application, and are therefore open-ended and do not exclude the presence of additional undescribed or unmentioned elements, materials, phases, or method steps. As used herein, "consisting of" should be understood in the context of the present application to exclude the presence of any unspecified elements, materials, phases, or method steps. As used herein, "consisting essentially of" should be understood in the context of the present application to include the specified elements, materials, phases, or method steps, and, where applicable, any unspecified elements, materials, phases, or method steps that do not substantially affect the basic or new features of the present invention.

[0052] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.

[0053] In addition, it should be understood that any numerical range mentioned herein is intended to include all sub-ranges contained therein. For example, a range of "1 to 10" is intended to include all sub-ranges between the mentioned minimum value of 1 and the mentioned maximum value of 10 (and including the minimum and maximum values), i.e., having a minimum value equal to or greater than 1 and a maximum value equal to or less than 10.

[0054] In this application, the use of the singular includes the plural, and the plural includes the singular, unless expressly stated otherwise. Furthermore, in this application, the use of "or" means "and / or" unless specifically stated otherwise, although "and / or" may be expressly used in some instances. In this application and the appended claims, the articles "a," "an," and "the" include plural referents unless expressly and unequivocally limited to one referent.

[0055] While specific embodiments of the present invention have been described above for purposes of illustration, it will be apparent to those skilled in the art that various changes may be made to the details of the invention without departing from the invention as defined in the appended claims.

Claims

1. A steel alloy resistant to hydrogen degradation comprising 15 to 30 wt. % Mn, 0.15 to 1 wt. % C and 0.05 to 3 wt. % Al, wherein the steel alloy has a microstructure comprising at least 99 volume % austenite and has a relative reduction in area of ​​not more than 20%.

2. The steel alloy according to claim 1, wherein C is greater than 0.2 wt. %.

3. The steel alloy according to claim 1, wherein Mn is greater than 18 wt. %.

4. The steel alloy according to claim 1, wherein when Mn is less than 18 wt. %, C is greater than 0.2 wt. %.

5. The steel alloy according to claim 1, wherein when C is less than 0.3 wt. %, Mn is greater than 18 wt. %.

6. The steel alloy according to claim 1, wherein Mn accounts for 18 to 25 wt. %, and C accounts for 0.3 to 1 wt. %.

7. The steel alloy according to claim 1, wherein Mn accounts for 20 to 24 wt. %, and C accounts for 0.4 to 0.6 wt. %.

8. The steel alloy of claim 1, further comprising 0.8 to 2.5 wt. % Ni.

9. The steel alloy of claim 1 further comprising at least 0.2 wt. % Cu.

10. The steel alloy of claim 1, further comprising 0.8 to 2.5 wt. % Ni and 0.2 to 2 wt. % Cu.

11. The steel alloy according to claim 10, further comprising at least 0.5 wt. % Si.

12. The steel alloy of claim 10, further comprising at least 1 wt. % Cr.

13. The steel alloy of claim 10, further comprising 0.5 to 4 wt% Si, and 1 to 3.5 wt% Cr.

14. The steel alloy of claim 1 further comprising at least 0.02 wt. % Ti.

15. The steel alloy according to claim 1, wherein Mn accounts for 20 to 24 wt. %, and C accounts for 0.3 to 0.6 wt. %.

16. The steel alloy according to claim 15, further comprising 0.8 wt% to 2.5 wt% Ni, and 0.2 wt% to 2 wt% Cu.

17. The steel alloy of claim 16, further comprising 0.5 to 4 wt. % Si, and 1 to 3.5 wt. % Cr.

18. The steel alloy of claim 17, wherein Al accounts for 1.4 to 1.8 wt%, Ni accounts for 1.2 to 1.5 wt%, Cu accounts for 0.6 to 1.2 wt%, Si accounts for 2 to 3.2 wt%, and Cr accounts for 2 to 3.2 wt%.

19. The steel alloy according to claim 18, further comprising 0.08 to 0.2 wt. % Ti.

20. The steel alloy of claim 1, wherein the microstructure comprises at least 99.5 volume % austenite.

21. The steel alloy of claim 1, wherein the relative reduction in area is less than 15%.

22. The steel alloy of claim 1, wherein the steel alloy has an ultimate tensile strength greater than 700 MPa, and a total elongation greater than 50%.

23. A method of producing the steel alloy of claim 1 comprising hot rolling the steel alloy to form a slab and cooling the slab.

24. The method of claim 23, further comprising subjecting the steel alloy slab to electrochemical charging to generate nascent atomic hydrogen.